Persilangan Genotipe-Genotipe Kedelai (Glycine max L. Merrill.) Hasil Seleksi pada Tanah Salin dengan Tetua Betina Varietas Grobogan - Nurul Ain Lubis; Rosmayati Rosmayati; Diana Sofia Hanafiah (Jurnal Agroekoteknologi, 2015)
The aim of the research was to cross the resistant generations of the saline soil from pedigreeselection of grobogan varieties with female parent of Grobogan varieties as one of the stage toobtain the varieties which resistant to the saline condition. The research was carried out in plastichouse Agriculture’s Faculty of North Sumatera University, Medan, Indonesia with ± 25 m altitudeabove sea level. which was held in April to July 2014. This research used Completely RandomizedDesign with five combination crossing and ten replicant that is Grobogan×N,Grobogan×N3, Grobogan×N4, Grobogan×N. Parameters observed were the percentage of thesucceeded crossing, number of productive pods, number of empty pods, number of pods containone seed, number of pods contain two seeds, number of pods contain three seeds, and weight of 10seeds per plant. The results showed that crossing between selected of soybean genotypes on salinesoil with Grobogan varieties as female parent significantly different for parameters number ofproductive pods, number of empty pods, number of pods contain one seed, number of pods containtwo seeds, number of pods contain three seeds, and weight of 10 seeds per plant, but notsignificantly different for parameters the percentage of the succeeded crossing.Key words : crossing, genotype soybean, saline soil. 51, Grobogan×N2